Fabrication of elastic, conductive, wear-resistant superhydrophobic composite material - Seyed Mehran Mirmohammadi (Nature Portfolio, 2021)
Abstract A polydimethylsiloxane (PDMS)/Cu superhydrophobic composite material is fabricated by wet etching, electroless plating, and polymer casting. The surface topography of the material emerges from hierarchical micro/nanoscale structures of etched aluminum, which are rigorously copied by plated copper. The resulting material is superhydrophobic (contact angle > 170°, sliding angle < 7° with 7 µL droplets), electrically conductive, elastic and wear resistant. The mechanical durability of both the superhydrophobicity and the metallic conductivity are the key advantages of this material. The material is robust against mechanical abrasion (1000 cycles): the contact angles were only marginally lowered, the sliding angles remained below 10°, and the material retained its superhydrophobicity. The resistivity varied from 0.7 × 10–5 Ωm (virgin) to 5 × 10–5 Ωm (1000 abrasion cycles) and 30 × 10–5 Ωm (3000 abrasion cycles). The material also underwent 10,000 cycles of stretching and bending, which led to only minor changes in superhydrophobicity and the resistivity remained below 90 × 10–5 Ωm.